PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Perkebunan dan Tanaman Pangan yang Terdaftar di BEI Periode 2018-2022) - Merlin Gowanti; Wahyu Meiranto (Diponegoro Journal of Accounting, 2023)
The objective of this research is to examine the effect of profitability, leverage, and firm size on firm value.The independent variables that used in this research are profitability, leverage, and company size while the dependent variable is firm value. The population in this study consists of plantation and food crop companies listed on the Indonesia Stock Exchange in the 2018-2022 period. The sample was determined by purposive sampling method with sample results of 95 company financial reports. Hypothesis testing in this research uses multiple regression analysis.The results of this study indicate that the variable profitability and firm size have a positive and significant effect on firm value. Meanwhile, the leverage variable has a negative effect on firm value.